PENGARUH FAMILY CONTROL, FIRM RISK, SIZE, DAN AGE TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN PADA SEKTOR PERDAGANGAN, JASA, DAN INVESTASI - Gunawan, Liany (Business Accounting Review, 2014)
This study conducted to know the influence of family control on the profitability and firmâs value. The sample used in this study were firms that have annual reports and complete research data on trade, service, and investment sectors of the period 2008-2011. The dependent variables in this study were the profitability and firmâs value, while the independent variable in this study was family control, in addition, the control variables used in this study were the firm risk, size, and age. The results of this study indicated profitability as the dependent variable showed that family control, firm risk, age had no influence on the profitability of the firm, while the size had significantly positive influence on the profitability of the firm. Meanwhile, the results of the research on the dependent variable of the firmâs value showed that family control and firm risk did not influence the firm value, while the size had significantly positive influence on firm value, and age had significantly negative influence on firmâs value.